Orthognathic treatment in Greig cephalopolysyndactyly syndrome: A case report - VAROL, ALTAN (ELSEVIER SCIENCE INC, 2019)
Typical Greig cephalopolysyndactyly syndrome (GCPS) is characterized by preaxial polydactyly or mixed preand postaxial polydactyly, true widely spaced eyes, macrocephaly. Individuals with mild GCPS may have subtle craniofacial findings. The diagnosis of GCPS is based on clinical findings and family history. GLI3 is the only gene known to be associated with GCPS. It has an autosomal dominant inheritance. The literature fails in documentations of any treatment protocol for defective jaw relationship in these patients. Therefore, we report on a patient with GCPS presenting polysyndactyly, frontal bossing, high forehead, skeletal Class III deformity due to maxillary retrognathism and mandibular prognathism, treated with orthognathic surgery by means of double jaw surgery and orthodontic treatment with fixed appliances.
Keywords: Orthognathic surgery; Greig syndrome; Double jaw surgery